Diagnostic accuracy of heart rate variability as a screening tool for mild neurocognitive disorder - Czopek-Rowinska, Julia; de Bruin, Eling D.; Manser, Patrick (Frontiers in Aging Neuroscience, 2024)
BackgroundMild neurocognitive disorder (mNCD) is recognized as an early stage of dementia and is gaining attention as a significant healthcare problem due to current demographic changes and increasing numbers of patients. Timely detection of mNCD provides an opportunity for early interventions that can potentially slow down or prevent cognitive decline. Heart rate variability (HRV) may be a promising measure, as it has been shown to be sensitive to cognitive impairment. However, there is currently no evidence regarding the diagnostic accuracy of HRV measurements in the context of the mNCD population. This study aimed to evaluate the diagnostic accuracy of vagally-mediated HRV (vm-HRV) as a screening tool for mNCD and to investigate the relationship between vm-HRV with executive functioning and depression in older adults who have mNCD.MethodsWe retrospectively analyzed data from healthy older adults (HOA) and individuals with a clinical diagnosis of mNCD with a biomarker-supported characterization of the etiology of mNCD. Diagnostic accuracy was evaluated using receiver operating characteristic curve analysis based on the area under the curve. Sensitivity and specificity were calculated based on the optimal threshold provided by Youden’s Index. Multiple linear regression analyses were conducted to investigate the relationship between vm-HRV and executive functioning and depression.ResultsThis analysis included 42 HOA and 29 individuals with mNCD. The relative power of high frequency was found to be increased in individuals with mNCD. The greatest AUC calculated was 0.68 (with 95% CI: 0.56, 0.81) for the relative power of high frequency. AUCs for other vm-HRV parameters were between 0.53 and 0.61. No consistent correlations were found between vm-HRV and executive functioning or depression.ConclusionIt appears that vm-HRV parameters alone are insufficient to reliably distinguish between HOA and older adults with mNCD. Additionally, the relationship between vm-HRV and executive functioning remains unclear and requires further investigation. Prospective studies that encompass a broad range of neurocognitive disorders, HRV measurements, neuroimaging, and multimodal approaches that consider a variety of functional domains affected in mNCD are warranted to further investigate the potential of vm-HRV as part of a multimodal screening tool for mNCD. These multimodal measures have the potential to improve the early detection of mNCD in the future.